Gap in STEM Education: Why is There a Decline in Women Participation? - Kenneth, Anthony (Universitas Terbuka, 2022)
A steady Gender gap is observed with the number of students enrolled in STEM (Science, Technology, Engineering, and Mathematics) fields in higher education and universities. The underrepresentation of women in the field of STEM is world-wide. Numerous studies have contemplated different factors for this gap and studies on interests showing, that women's career decisions are often influenced by their interest which is inclined towards working Ã¢â‚¬Ëœwith peopleÃ¢â‚¬â„¢ and deviates them from STEM. Men prefer to work with Ã¢â‚¬Ëœmaterial and gadgetsÃ¢â‚¬â„¢ which interests more men towards STEM. Increment in Ã¢â‚¬Å“enterprising and artistic interestsÃ¢â‚¬Â among the women, less awareness on the career and study opportunities, lesser female mentors, the duration to become an expert in STEM, lesser encouragement from the opposite sex, has an impact on the number of females in STEM. The gap was more prominent in egalitarian countries and termed as the Ã¢â‚¬Å“education gender-equality paradoxÃ¢â‚¬Â. The difference in early childhood spatial ability can also contribute to the emergence of gender differences in mathematics and science later. This article also suggests more research into making STEM attractive for both genders, providing early education that provides makes STEM attractive for both genders.